Transition metal control in the reaction of alkyne-substituted phenyl iodides with terminal alkynes: Sonogashira coupling vs cyclic carbopalladation - Teplý, Filip; Stará, Irena G.; Starý, Ivo; Kollárovič, Adrian; Šaman, David; Fiedler, Pavel (Tetrahedron, 2002)
Reaction between terminal alkynes and phenyl iodides bearing a tethered alkyne unit can be effectively controlled by the nature of a transition metal catalyst. Whereas the use of Pd(0)/Cu(I) promotes the expected Sonogashira coupling to give phenyl alkynes, the absence of the copper co-catalyst triggers a palladium-mediated cyclisation providing 1,2-dihydroacenaphthylene, 1 H,3 H-benzo[ de]isochromene, (1 Z)-1-(2-propynylidene)-2,3-dihydro-1 H-indene and (4 E)-4-(2-propynylidene)-3,4-dihydro-1 H-isochromene derivatives. In the latter Pd-catalysed two-component process, the product distribution depends on the structure of alkyne-substituted phenyl iodides, terminal alkynes and secondary amines used as solvents. The proposed reaction mechanism reflects a competitive formation of intermediary σ-(acetylide) vs π-alkyne Pd(II) complexes. Graphic